Rhododendron javanicum (Blume) Benn. AND Rhododendron sessilifolium J.J. Sm. GERMINATION AND SEEDLINGS DEVELOPMENT ON DIFFERENT GROWING MEDIA AND FERTILIZERS APPLICATION - Rahman, Wiguna; Juairiah, Lina (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2013)
Growing medium is one of the most important factor for ex situ conservation of Rhododendron. Study on different growing media available locally were conducted for germinating and developing the seedlings of Rhododendron javanicum and R. sessilifolium. Tree fern roots medium was suitable for germination and developing Rhododendron javanicum and R. sessilifolium seedlings. Growing medium for bigger seedlings using